Investigation into gyneco-pathological disorders and identification of associated bacteria from the genital organs of cows in Dinajpur, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was aimed to investigate the gynaeco-pathological disorders by post-mortem and histopathological examination, and to identify the associated bacteria. A total of 310 genital tracts of cows were collected from slaughter house of Dinajpur Sadar Upazilla during April 2009 to March 2010. Among the 310 samples, 31.29% (n=97/310) were affected with endrometritis. Similarly, 8.37% (n=26/310) cystic ovary, 6.77% (n=21/310) ovary hyperplasia, 4.84% (n=15/310) pyometra, 4.84% (n=15/310) parovarian cyst, 4.52% (n=14/310) hydrometra, 4.84% (n=15/310) ovary hypoplasia, 3.55%(n=11/310) ovaro-bursal adhesion, 1.29% (n=4/310) vaginal cyst and 0.66% (n=2/310)) hemorrhagic uterine horn were detected by post-mortem examination, the cases were reconfirmed by histopathological studies. Uterine fluid (n=50) samples were collected, and were subjected for conventional bacteriological culture and biochemical analysis. Escherichia coli and Salmonella sp. could be identified from 30% (n=15/50) and 8% (n=4/50) samples, respectively. In conclusion, various pathological disorders in the female reproductive system of cows are prevalent, that may cause reduction of calf production.http://dx.doi.org/10.5455/javar.2015.b76